2021
DOI: 10.1111/jocs.15862
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics, management, and outcomes among admissions for primary cardiac tumors: Results from the National Inpatient Sample

Abstract: Introduction: Primary cardiac tumors (PCT) are rare, and their contemporary outcomes are not well characterized in the literature. We assessed temporal trends in patient characteristics and management of admissions for PCT in US hospitals. Methods: Admissions with the principal diagnoses of a PCT (benign neoplasm of heart: ICD-9 212.7, ICD-10 D15.1; malignant neoplasm of heart: ICD-9 164.1, ICD-10 C38.0) between 2006 and 2017 were extracted from the National Inpatient Sample. Trends in demographics and clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…The longitudinal European multicenter study reported early mortality of 4.5% in 89 children ( 10 ). The National Inhospital Sample database in the United States recorded 186 (1.5%) in-hospital mortalities among 12,811 cases of surgically managed PCT ( 17 ). Few studies have reported long-term outcomes following PCT resection, especially in pediatrics.…”
Section: Discussionmentioning
confidence: 99%
“…The longitudinal European multicenter study reported early mortality of 4.5% in 89 children ( 10 ). The National Inhospital Sample database in the United States recorded 186 (1.5%) in-hospital mortalities among 12,811 cases of surgically managed PCT ( 17 ). Few studies have reported long-term outcomes following PCT resection, especially in pediatrics.…”
Section: Discussionmentioning
confidence: 99%
“…A relative increase in the utilization of population-based databases to study sociodemographic features of PMCTs has been seen in recent years ( 11 , 12 ). A study conducted by Heaton et al on the National Inpatient Sample showed higher in-hospital mortality in Hispanic patients as compared to Whites in a multivariable analysis ( p = 0.03) ( 13 ). Oliveira et al compared incidences of cardiac and non-cardiac tumors in White, Black, and “Other” races in SEER and found a significantly higher incidence of mesotheliomas of cardiac origin in the Black population (15.9 vs. 4.9%) ( 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…In patients with a medical group, probably not all patients received chemotherapy. 1 It might be informative to stratify the medical group into those with and without chemotherapy to investigate the outcomes of chemotherapy.…”
mentioning
confidence: 99%
“…The authors reported that the existence of atrial fibrillation was associated with undergoing the surgery. 1 Atrial fibrillation is in general associated with high age and comorbidity such as heart failure, hypertension, and diabetes mellitus, all of which would be surgical high-risk factors. Could the authors explain the mechanism why those with atrial fibrillation tended to receive surgery?…”
mentioning
confidence: 99%
See 1 more Smart Citation